Adolescent Susceptibility to E-Cigarettes: An Update From the 2018 National Youth Tobacco Survey. Issue 4 (May 2021) - Tackett, Alayna P.; Keller-Hamilton, Brittney; Hébert, Emily T.; Smith, Caitlin E.; Wallace, Samantha W.; Stevens, Elise M.; Johnson, Amanda L.; Wagener, Theodore L.
Purpose: Examine correlates of e-cigarette susceptibility among adolescents. Design: Secondary data analyses using the 2018 National Youth Tobacco Survey, excluding participants under 12 and over 17. Setting: United States middle and high schools. Subjects: Never e-cigarette users ( n = 12, 439) ages 12-17. Measures: Relationships between e-cigarette susceptibility and age, sex, race/ethnicity, ever tobacco use, perceived ease of purchasing tobacco products, perceived harm, relative addictiveness, household use of e-cigarettes/tobacco were examined. Analysis: Odds of susceptibility were modeled with weighted multivariable logistic regressions. Results: Thirty-five percent (unweighted n = 4, 436) of adolescents were susceptible to e-cigarettes. Adolescents who were female (aOR = 1.2), Hispanic (aOR = 1.3), perceived e-cigarettes as anything less than "a lot of harm" (aOR = 2.2-4.9) and "easy" to purchase (aOR = 1.4), had ever used combustible tobacco (aOR = 2.9), or reported household use of e-cigarettes (aOR = 1.5) were susceptible. Non-Hispanic black respondents (vs. non-Hispanic white; aOR = 0.72) had significantly lower odds of susceptibility to e-cigarettes. Conclusion: In the 2018 NYTS adolescent sample, perceptions of harm and ease of tobacco product purchase appear to be significantly related to higher odds of e-cigarette susceptibility, in addition to other demographic factors. Longitudinal data, particularly cohort data following adolescents from susceptible to actual or no use, are needed to assess predictors of e-cigarette use initiation.